2009
DOI: 10.1021/ma901313a
|View full text |Cite
|
Sign up to set email alerts
|

Phase Behavior of Polystyrene-b-poly(methyl methacrylate) Diblock Copolymer

Abstract: The phase behavior of polystyrene-b-poly(methyl methacrylate) (PS-b-PMMA) copolymers of various molecular weights has been studied by using small-angle X-ray scattering (SAXS) and depolarized light scattering (DLS). The empirical Flory χ, determined from scattering intensity profiles for a fully disordered PS-b-PMMA copolymer, was shown to behave differently depending on temperature range. χ was described mostly by enthalpic contribution at higher temperatures, but a dominant entropic contribution appeared in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
49
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 47 publications
1
49
0
2
Order By: Relevance
“…Topographical [46][47][48] or chemical pre-pattering [49,50] of the substrate allows registering the in-plane orientation of the nanodomains thus further improving the lateral order. While PS-b-PMMA copolymers show a remarkable technological potential, their low χ AB value (0.06 at 300 K) [51] limits the minimum domain dimension to approximately 12 nm [52,53]. Consequently, DBCs with higher χ AB were developed scaling down the domain resolution well below 10 nm.…”
Section: Bcps Backgroundmentioning
confidence: 99%
“…Topographical [46][47][48] or chemical pre-pattering [49,50] of the substrate allows registering the in-plane orientation of the nanodomains thus further improving the lateral order. While PS-b-PMMA copolymers show a remarkable technological potential, their low χ AB value (0.06 at 300 K) [51] limits the minimum domain dimension to approximately 12 nm [52,53]. Consequently, DBCs with higher χ AB were developed scaling down the domain resolution well below 10 nm.…”
Section: Bcps Backgroundmentioning
confidence: 99%
“…More recently, Ahn et al [15] have studied the phase behaviour of polystyrene-b-poly(methyl methacrylate) (PS-b-PMMA). In the case of poly(styrene-co-alkyl acrylate) copolymers, the acrylate monomers have a dielectric strength one hundred times higher that of the styrene monomers [16]).…”
Section: Introductionmentioning
confidence: 99%
“…For the last two decades, χ for this system has been known to possess a strong entropic a with a weak enthalpic b. [5][6][7][8] It was not until a year ago that a hidden truth regarding χ for this system was found: 9 For the PS-b-PMMA copolymer melt of M n =20,000, χ S-MMA at lower temperatures was shown to be similar to literature values, but that at higher temperatures reveals a strong enthalpic b on the contrary. Further investigation of order-disorder transition temperatures for the copolymers of various chain sizes was found to support also the enthalpically domi-…”
Section: Introductionmentioning
confidence: 99%
“…8 Meanwhile, the present author and co-workers reconsidered the whole problem for PS-b-PMMA. 9 They measured SAXS for the disordered copolymer and those exhibiting ordering transition temperatures with finely tuned molecular weights. It was found that χ for the copolymer possesses two different stages as It is seen that χ at lower temperatures is similarly anomalous to those reported previously, but χ at higher temperatures is more or less like those for typical block copolymers such as PS-b-polyisoprene, 18 which is enthalpically oriented.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation